Testing trade-off theory and pecking order theory under managerial overconfidence - Elżbieta Bukalska (International Journal of Management and Economics, 2019)
We address our research to the problem of managerial overconfidence and financing behavior. The aim of the paper is, hence, to ascertain the pattern of financing decisions of overconfident managers and identify the relevant capital structure theory (trade-off or pecking order theory) that can be used to explain financing decisions of overconfident managers. We collected a sample of 145 private companies. The degree of overconfidence was distinguished by surveying the managers on overestimation, overplacement, and overoptimism. The financial data covers the period of 2010-2015. We calculated static ratios of capital structure and uncovered the determinants of capital structure. We then unveiled the target debt ratios using Fama and French methodology and identified the difference between target and actual debt ratios. We also calculated the value of deficit and the sources of financing according to Shyam-Sunder and Myers. We found that the companies managed by overconfident managers use higher value of equity and display similar debt ratios. They also utilize reverse pecking order preference-trying to use internal funds and then turning to equity. Moreover, we noted that companies managed by overconfident managers come closer to target debt ratios and implement more risky fixed assets financing strategies. The significance of our research is that we contribute to the understanding of capital structure decisions by taking into account behavioral biases and conducting comprehensive research on both static and dynamic capital structure.
Keywords: G32; G40; 650; trade-off theory; pecking order theory; overconfident managers